PEMBELAJARAN MENGANALISIS TEKS CERITA PENDEK DENGAN MENGGUNAKAN METODE HYPNOTEACHING - Santi Susanti; Lia Yuliantini; Ika Mustika (IKIP Siliwangi, 2018)
The problem of this research is the learning plan, the implementation of learning, and the learning result of analyzing short story text using the Hypno-teaching method on the students of class XI SMAN 15 Bandung. The method of this research is descriptive. The research technique is an observation and test sheet. The population of this study is all the results of the ability to analyze the intrinsic element of short stories of students from XI MIPA 1 to XI MIPA 5 in SMAN 15 Kota Bandung, amounting to 215 students, and the sample is amounting to 31 students of class XI MIPA 5. The result of the research shows that: 1) learning planning to analyze short story text by using the Hypno-teaching method prepared by the teacher is appropriate, 2) implementation of learning done by teacher in accordance with RPP, 3) learning result analyze short story text using the Hypno-teaching method indicated from preliminary tests with an average score of 66.80 or 66.80%, and the final test score averaged 78.23 or 78.23%. The increase is 11.42%. In conclusion, effectiveness the Hypno-teaching method is used as a learning method in analyzing short stories.